LA HISTORIA Y LA TRADICIÓN. RAZÓN Y SENTIMIENTO ABORDAN EL TIEMPO - Sánchez Ferra, Anselmo José (Antigüedad y Cristianismo, 1995)
History and myth, from an anthropological perspective, are concepts which have different vision of the world and we cannot include them in an evolutive sequence in which one generates the other. They are two different perspectives of reality, sometimes antagonistic and other times complementary. The author suggests a reflexion on the realionship between the two, not only on an intelectual level, but alsothe level of everyday life.